2016
DOI: 10.1016/j.watres.2015.10.046
|View full text |Cite
|
Sign up to set email alerts
|

A multi-stable isotope framework to understand eutrophication in aquatic ecosystems

Abstract: 10Eutrophication is a globally significant challenge facing aquatic ecosystems, associated with human 11 induced enrichment of these ecosystems with nitrogen (N) and phosphorus (P). However, the limited 12 availability of inherent labels for P and N has constrained understanding of the triggers for 13 eutrophication in natural ecosystems and appropriate targeting of management responses. This paper 14 proposes and evaluates a new multi-stable isotope framework that offers inherent labels to track 15 biogeochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 63 publications
5
86
3
2
Order By: Relevance
“…The 3.5‰ fluctuation of  18 O PO4-Drain within the monitored storm event was significant given the amount of variation in phosphate isotope signatures reported in previous studies. For example, Gooddy et al (2016) found that  18 O PO4 values over a 200 m stream reach with multiple source inputs, including a wastewater treatment plant and livestock farm, only varied by 2.0‰ to 2.8‰ during low flow and high flow sampling, respectively. Similarly, during a longitudinal river survey in southwest England, Granger et al (2017) found that  18 O PO4 signatures in tributaries and along the main stem of the river only varied by 1.7‰.…”
Section: Intra-event Variability Of Tile Drain Phosphate Oxygen Isotomentioning
confidence: 99%
“…The 3.5‰ fluctuation of  18 O PO4-Drain within the monitored storm event was significant given the amount of variation in phosphate isotope signatures reported in previous studies. For example, Gooddy et al (2016) found that  18 O PO4 values over a 200 m stream reach with multiple source inputs, including a wastewater treatment plant and livestock farm, only varied by 2.0‰ to 2.8‰ during low flow and high flow sampling, respectively. Similarly, during a longitudinal river survey in southwest England, Granger et al (2017) found that  18 O PO4 signatures in tributaries and along the main stem of the river only varied by 1.7‰.…”
Section: Intra-event Variability Of Tile Drain Phosphate Oxygen Isotomentioning
confidence: 99%
“…A decline in water quality and the degradation of aquatic ecosystems are often accompanied by rapid agricultural and economic development [1][2][3]. Eutrophication, as an important contributor to the degradation of aquatic ecosystems, is the enrichment of water bodies by nutrients, especially compounds of nitrogen (N) and phosphorus (P), which may cause the accelerated growth of algae and higher forms of plant life and produce an undesirable disturbance to the balance of organisms and water quality [4].…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of this study are to: (1) assess the water quality and potential ecological risk of heavy metals in the Haihe River Basin; (2) explore and understand the synergic pollution characteristics of surface water quality and heavy metal pollution in sediments; and (3) identify the driving forces that cause eutrophication, the potential ecological risk of heavy metals and their synergic pollution in the Haihe River Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Si le phosphore constitue l'un des éléments nutritifs majeurs pour les écosystèmes aquatiques, il n'en demeure pas moins que sa présence excessive dans ces entités est l'une des causes principales de l'eutrophisation. Dans ce fléau écologique, il est incriminé en tant que cofacteur limitant avec l'azote (GOODY et al, 2016;KASPERSEN et al, 2016;ROLLAND et al, 2015;ULRICH et al, 2016). Il en est le facteur de maîtrise du fait de son cycle biogéochimique (ABEL et al, 2010;YAO, 2011).…”
Section: Introductionunclassified